L’évolution récente du transport de marchandises en Belgique - Mathieu Strale (EchoGéo)
Belgium has been an important hub for freight transport in Europe for a long time. The rapid growth of world trade and the free market policy create many new challenges for this activity. Thisarticleaddresses theissuebyadual approach, on one hand theinsertion ofBelgium intheinternational transport networksand the other handtransport developments inside the country. Belgium seems to fully succeed in this new environment. Its terminals have grown rapidly, hosting major global carriers and the country has become a major logistics hub. However, this trend generates many new social, environmental and economic issues that seem largely ignored.